ANALYSIS OF DISCRETE DATA USING LINEAR REGRESSION - J. Flowers, Robert (Ecosistemas y Recursos Agropecuarios, 2014)
Maximum likelihood estimates are obtained for a linear regressio model where the dependent variable is a linear transformation of mutinomially distributed random variables.
Keywords: Multinomial distribution; maximum likelihood estimation; minimum modified chi-square estimation; models of marginal homogeneity; binomial regression